Maternal determinants of dietary patterns in infancy and early childhood in the Growing up in New Zealand cohort - Teresa Gontijo de Castro; Amy Lovell; Leonardo Pozza Santos; Beatrix Jones; Clare Wall (Scientific Reports, 2023)
Abstract Given the importance of diet in early life, assessing children’s diet is crucial to guide interventions. Using data from a nationally generalizable New Zealand (NZ) birth cohort we examined children’s dietary patterns at 9- (n = 6259), 24- (n = 6292), and 54-months (n = 6131), and their association with maternal sociodemographic and health behaviours. At each time-point, children's dietary patterns were identified using principal components analysis. We then used multivariate linear regression to examine associations between each pattern and maternal variables. At 9-, 24- and 54-months, two dietary patterns were identified, explaining 36.4%, 35.3% and 33.6% of children's intake variability, respectively. Refined high in sugar, salt and fat dietary pattern, at all time-points, was characterized by high positive loadings in white/refined breads and cereals, and items with high sugar, sodium, and fat content. At 24-months, Refined high in sugar, salt and fat also included a high positive loading with protein food groups. Fruit and vegetables dietary pattern, at all time-points, had high positive loadings for fruits and vegetables (with type varying across time-points). Fruit and vegetables also included high loading in whole grain options of breads and cereals at 24-months and the protein food group was part of this dietary pattern at 9- and 54-months. Children’s scores on the Refined high in sugar, salt and fat pattern had strong associations with maternal smoking habits, education level, ethnicity, and maternal scores in the “Junk” and “Traditional/White bread” dietary patterns (constructed from an antenatal interview). Children’s scores on the Fruit and vegetables pattern had strong associations with the maternal scores in the dietary pattern “Health Conscious”. Interventions to improve diet in early life in NZ need to be responsive to ethnicity and suitable for people of all education levels. Interventions that improve maternal health behaviours may also improve children’s diet.